Single-tree management for high-value timber species in a cool-temperate mixed forest in northern Japan. Issue 1 (2nd January 2016) - Owari, Toshiaki; Okamura, Koji; Fukushi, Kenji; Kasahara, Hisatomi; Tatsumi, Shinichi
ABSTRACT: High-value hardwood species such as monarch birch ( Betula maximowicziana ) and castor aralia ( Kalopanax septemlobus ) are important economic and ecological elements of cool-temperate mixed forests in northern Japan. This article presents the single-tree management system for high-value timber species as practised for 50 years at the University of Tokyo Hokkaido Forest. Nearly 2000 valuable broad-leaved trees meeting the size and quality criteria have been registered as 'superior trees', and their status is periodically monitored for timing of harvest. A case study was conducted using 2105 inventory plots to characterize the stand types in which superior trees occur. A total of 57 superior trees of 11 broad-leaved species was found in 2.2% of the inventory plots. The results indicated that superior trees generally grew in mature species-rich stands. Superior trees of some species may have promoted their abundance by dispersing relatively more seeds to the surroundings. Single-tree management facilitates the sustainable use of high-value timber species by explicitly monitoring the numbers, attributes and locations of superior trees, and contributes to conserving stand structural diversity through protection of these large-sized canopy trees, which promotes ecological values such as biomass and carbon storage, species diversity, seed abundance and bird habitat. The production of fancy wood from superior trees earns significant income through extremely high log prices (maximum > 20, 000 USD m –3 ). EDITED BY Nicholas Brokaw